O mito das Amazonas : uma discussão psicanalítica sobre a feminilidade - Souza, Ivy Semiguem Freitas de (2012)
This study proposes a psychoanalytic discussion about femininity by taking the myth of the Amazons as the main material. In this narrative, we come across the account of a society of warriors formed almost exclusively by women, who do not allow the entry of men in their territory (Brandão, 1991a). Thus, proposing that the myth emphasizes the theme of femininity, we begin from the Freudian view about female sexuality to analyze it through some topics, such as: castration, the relationship of the warriors with men and hysterical fantasies. Subsequently, we continue our discussion by introducing the concept of gender from Laplanche's Theory of the General Seduction. In this theory, gender is thought through a notion of plurality. For that we use Laplanche's view on myth, which, unlike Freud's, understands that the myth works as an organizer for the sexual and, therefore, can be found on repression's side. From this point of view, we seek to untranslate the myth through two perspectives: a feminist's point of view, like Dio Bleichmar and Mitchell, who defend that there is a disparity in the social value of the genders that produces consequences for femininity; and Dejours' perspective, who proposes the relationship of domination-servitude in genders as linked within the residual attachment. Accordingly, we observe that the Amazon women may acknowledge another translation of femininity and that they may be noticed as a fertile material to think the translation possibilities in the process of femininity and gender constitution. Lastly, we propose that, although it is possible that exists a prototype of a relation of dependence in the foundation of the psyche that was originated in the Fundamental Anthropological Situation and that extend itself to gender issues, it would still be possible to reach that resistant content of domination-servitude and advance by means of more flexible translations that concerns gender manifestations.